Mastitis Incidences and Antibiotic Resistance in Bovines in Uasin Gishu County, Kenya - Nyakiti, A. A. O.; Oliech, G. W. O.; Osano, O. (Africa Environmental Review Journal, 2022)
Mastitis is an inflammatory reaction induced by a bacterial infection of the udder tissue. Bovine mastitis is one of the terrible diseases that causes enormous losses to the global dairy business. Antimicrobial-resistant (AMR) bacteria on farms in developing countries, where the bulk of livestock is kept on smallholdings, are poorly understood. There is a need to understand the factors that contribute to the increased occurrence of mastitis in order to control it. Consequently, this study evaluated mastitis incidences and antibiotic resistance in Bovines in Uasin Gishu County, Kenyan. A random sample consisting of one hundred and fifty lactating dairy cows; fifty each from three purposively chosen study sites, from several dairy farms across Uasin Gishu County- Kenya were tested in a study of mastitis. Causative microbes were identified both by cultural morphology and biochemical tests. Culture and sensitivity testing using the disc diffusion method were done to determine their in vitro resistance to various antimicrobial agents. The Draminski Mastitis Detector was used to screen udder quarters for subclinical mastitis while a strip cup and visual examination were used to detect visible changes to the udder and /or the milk for clinical mastitis. Out of the 76 positive samples obtained at screening, 72 had bacterial growth while 4 had none. The bacterial or fungal genus isolated were Staphylococcus sp 31.6%, followed by Escherichia sp 22.4%, Klebsiella sp 18.4%, Streptococcus sp 17.1%, Corynebacterium sp 2.6%, Pseudomonas sp 1.3% and Candida sp 1.3%. Resistance by the isolated microbes was greatest to the two sulphonamides; sulphamethoxazole 17.3% and cotrimoxazole 17.3%, followed by chloramphenicol 16.6%, nalidixic acid 15.9%, ampicillin 15.2%, tetracycline 11.2%, streptomycin 5.1%, kanamycin 2.8% and gentamicin 2.2% in that decreasing order. In order to alleviate this problem of increase in antimicrobial resistance, the study recommended that cases detected are promptly and vigilantly treated with suitable antimicrobials after culture and sensitivity tests have been carried out.